Multimodal Literacy and Creative Teaching Practices of Public Elementary School Teachers - , Mariebeth S. Rocamora; , Josephine B. Baguio (Archives of Current Research International, 2025)
This study aimed to determine the significant relationship between multimodal literacy and creative teaching practices among public elementary school teachers in Mati Central District, Division of Davao Oriental. A descriptive-correlational research design was employed, involving a sample of 193 teachers from public elementary schools. Standardized questionnaires were administered through face-to-face surveys to collect data. The mean, standard deviation (SD), Pearson product-moment correlation, and multiple linear regression analyses were used for analysis. The findings revealed that multimodal literacy and creative teaching practices were both at very extensive levels. Correlation analysis indicated a significant relationship between multimodal literacy and creative teaching practices. Additionally, specific domains of multimodal literacy, such as expressing oneself using multimodal structures, interpreting content presented in multimodal forms, and preferring multimodal structures, significantly influenced creative teaching practices. These findings underscore the growing importance of integrating multimodal approaches in teacher development programs. The study contributes to the field of educational research by demonstrating how multimodal literacy can serve as a foundational skill that enhances pedagogical creativity. It provides empirical evidence supporting the alignment of multimodal competencies with 21st-century teaching demands. Promoting multimodal literacy through targeted professional learning can equip teachers to deliver instruction that is more dynamic, inclusive, and responsive to diverse learners in contemporary classrooms.